Rice bran oil - Macalalad, Jacinto C.; Mata, Nicolas D. Jr.; Valdezco, Jesus L. (Diliman, Quezon City College of Engineering, 1964)
Capacity: 5 tons/day -- Land area: 6,500 sq.m. -- Fixed capital investment: 6,435,898.80 -- Operating cost at maximum production: 2,059,326.25 -- Annual sales at maximum production: 2,880,000.00 -- Pay-off time: 9.95 years -- Break-even point: 2.34 tons/day -- Shut-down point: 0.86 ton/day
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Agricultural processing plants; Rice oil industry